Plasma calcium concentration during detoxification predicts neural cue-reactivity and craving during early abstinence in alcohol-dependent patients - Bach, Patrick; Schuster, Rilana; Koopmann, Anne; Vollstädt-Klein, Sabine; Spanagel, Rainer; Kiefer, Falk (European archives of psychiatry and clinical neuroscience, 2022)
Recent studies on the pathophysiology of alcohol dependence suggest a link between peripheral calcium concentrations and alcohol craving. Here, we investigated the association between plasma calcium concentration, cue-induced brain activation, and alcohol craving. Plasma calcium concentrations were measured at the onset of inpatient detoxification in a sample of N = 115 alcohol-dependent patients. Alcohol cue-reactivity was assessed during early abstinence (mean 11.1 days) using a functional magnetic resonance imaging (fMRI) alcohol cue-reactivity task. Multiple regression analyses and bivariate correlations between plasma calcium concentrations, clinical craving measures and neural alcohol cue-reactivity (CR) were tested. Results show a significant negative correlation between plasma calcium concentrations and compulsive alcohol craving. Higher calcium levels predicted higher alcohol cue-induced brain response in a cluster of frontal brain areas, including the dorsolateral prefrontal cortex (dlPFC), the anterior prefrontal cortex (alPFC), and the inferior (IFG) and middle frontal gyri (MFG). In addition, functional brain activation in those areas correlated negatively with craving for alcohol during fMRI. Higher peripheral calcium concentrations during withdrawal predicted increased alcohol cue-induced brain activation in frontal brain areas, which are associated with craving inhibition and cognitive control functions. This might indicate that higher plasma calcium concentrations at onset of detoxification could modulate craving inhibition during early abstinence.